146 Alloantigen-specific Tr1 cells designed to prevent GvHD have a distinct molecular identity and suppress through CTLA-4 and PD-1. (9th November 2020) - Cepika, Alma-Martina; Chen, Pauline P; Uyeda, Molly; Cieniewicz, Brandon; Narula, Mansi; Amaya, Laura; Louis, David M; Xu, Liwen; Ji, Xuhuai; Bertaina, Alice; Agarwal-Hashmi, Rajni; Davis, Mark M; et al.
Abstract : Background: Graft-vs-host-disease (GvHD) is a life-threatening complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT), limiting the use of this potentially curative treatment for hematological malignancies. To address this, we have developed T-allo10 cell therapy, which is enriched with type 1 regulatory T (Tr1) cells. Tr1 cells are peripherally inducible, CD49b+LAG3+IL-10+FOXP3- regulatory T cells that can confer alloantigen-specific tolerance, making them an attractive alternative to existing GvHD therapies, which non-discriminately impair both GvHD and protective immunity. T-allo10 cells are currently being evaluated in a phase I clinical trial in patients with hematological malignancies undergoing allo-HSCT (NCT03198234 ). Herein, we aimed to confirm that Tr1 cells are the active ingredient responsible for the T-allo10 suppressive function, and reveal the underlying molecular signatures to elucidate the mechanisms of Tr1 cell-mediated suppression. Methods: T-allo10 cells were generated in a co-culture of healthy host or patient tolerogenic dendritic cells (DC-10) with allogeneic healthy donor CD4+ T cells, then tested for Tr1 phenotype, anergy, suppression and cytokine production. Sorted T-allo10-derived Tr1 cells and non-Tr1 cells, as well as control effector T cells (Teff) and parental CD4+ T cells, were analyzed by TCR- and RNA-seq. Protein expression for key differentially expressed genes were validated, and the functional roles for IL-10, CTLA-4 and PD-1 in T-allo10-mediated suppression were confirmed in a suppression assay. Results: We show that the T-allo10 cell product is: i) enriched for Tr1 cells, ii) anergic in response to alloantigen re-challenge, but not to non-specific stimuli or 3rd party antigens, and iii) suppresses host-reactive T cells, but not T cell responses to other antigens. Furthermore, T-allo10-derived, isolated Tr1 cells had a restricted TCR repertoire, suggesting they clonally expand in response to alloantigens. T-allo10-derived Tr1 cells have a distinct signature compared to non-Tr1 cells, and, in addition to IL-10, express high levels of CTLA-4 and PD-1 (but not FOXP3). Notably, blockade of CTLA-4 and the PD-1 pathway completely abolishes T-allo10-mediated suppression of T cell responses. Conclusions: Our data shows that Tr1 cells are the active, suppressive, and antigen-specific ingredient of T-allo10 cells. Furthermore, while the role of IL-10 in Tr1 cell-mediated suppression is well known, we uncover that Tr1 suppress in addition through CTLA-4 and PD-1. Collectively, these intriguing findings underscore the importance of CTLA-4 and PD-1 pathways in conferring cell-mediated immunological tolerance. Further, they define the key characteristics and modes of action of antigen-specific Tr1 cells, providing crucial information for the ongoing T-all10 trial and future design of novel Tr1 cell-based therapies. Ethics Approval: The patient study was approved by Administrative Panels on Human Subjects in Medical Research, Stanford University, Tallo10 eProtocol # 38734. Healthy donor samples were purchased as deidentified human blood products from the Stanford Blood Center, and are thus exempt.